The last battle [compact disc, unabridged] - Lewis, C. S. (Clive Staples), 1898-1963 (Lewis, C. S. (Clive Staples), 1898-1963. Chronicles of Narnia, 2004)
Tirian, the last king of Narnia, is forced to make a stand against an Aslan imposter who raises forces both from within the land and without. Jill Pole and Eustace Scrubb are summoned to Narnia to help and ultimately to witness the last events.